First Report: Spodoptera Picta Guerin-Meneville, Armyworm on Swamp Lily (Crinum x powellii ‘Album’) in Bogor, Indonesia - Nadzirum Mubin; Khalisa Sasti Andina; Bela Hasna Audia (Universitas Andalas, 2023)
Armyworms are very common and can attack all types of plants. Attacking ornamental plants such as flowers is no exception. This study aimed to determine the types of fall armyworms that attacked lilies in a Bogor, West Java house. It turned out to be an obvious symptom of the attack, the leaves became bald, attacked from the leaves to the base of the stem, and the dirt and the previous attack became wet. Armyworm larvae are dark grey, with eye-catching yellow stripes in the late larval stage. The larvae and adults were identified as a group of armyworms of Spodoptera picta (Lepidoptera: Noctuidae). They are common in Australia, and they attack lilies. Characteristics of the larvae were dark grey with a longitudinal black line, a striking yellow line that runs along the middle of the dorsal, and a Y shape in the head. The female of S. picta lays eggs in groups ranging from 50 to 218 eggs per egg group with an egg size of 1 mm. Lili armyworm larvae have 5 stages with larval sizes of 2, 5, 15, 28, and 46 mm respectively. Meanwhile, the size of the pupa and imago of S. picta was 23 and 20 mm, respectively. The management of S. picta armyworms needs to be done so as not to cause major damage and losses to ornamental flower crops.